The survival processing advantage in memory using virtual reality versus traditional desktop display: Does it make a difference? - Bonin, Patrick; Méot, Alain; Argon, Stéphane; Boucheix, Jean-Michel; Thiebaut, Gaëtan (Memory & Cognition, 2026)
The survival processing advantage refers to the fact that words processed in relation to survival (e.g., finding food) are memorized better than words processed in a context that is not evocative of survival (e.g., moving to a foreign country). This effect has been extensively studied in laboratory tasks in which participants have to imagine a survival situation rather than being placed in a "supporting perceptual context." In the present study, we aimed to investigate the survival effect using virtual reality and compare it with a traditional desktop display. Using virtual reality technology, we replicated the survival processing advantage found in Wang et al.'s (Survival processing advantage demonstrated with virtual reality-based survival environment: A promising tool for survival processing research. Memory & Cognition, 51[1], 129–142, 2023) study. More importantly, the survival effect obtained with virtual reality was no greater than that obtained using more conventional means (i.e., a desktop display). The findings are discussed in relation to the issue of the optimality of the survival effect and the way proximate mechanisms are involved.